Ways to Teach Students to Independent, Creative Thinking Through Practical Activities - Madgʻafurova Dilfuza Ohunovna (Genius Journals, 2022)
This article is about ways of teaching students to self-study, creative thinking through organizing practical lesson with innovative technologies at higher educational organization. This article describes the problem of increasing the self activite of the assimilation of knowledge independent thinking by organizing self-education in higher educational institutions.
Keywords: Practical lessons; free thinking; activities; thinking